2009
DOI: 10.1158/1055-9965.epi-09-0596
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Incidence and Postmenopausal Hormone Use by Type, Recency, and Duration in Cancer Prevention Study II

Abstract: The Women's Health Initiative randomized trials showed a reduction in colorectal cancer risk with the use of estrogen plus progesterone (E + P), but not with estrogen alone (E-only), after intervention periods <7 years. Using data from the Cancer Prevention Study II Nutrition Cohort, we examined associations of colorectal cancer risk with E-only and E + P, including analyses by recency and duration of hormone use. During 13.2 years of follow-up, 776 cases of invasive colorectal cancer occurred among 67,412 pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 39 publications
4
33
0
1
Order By: Relevance
“…1). 4,5,13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Figure 2 shows the RR estimates reported by individual studies as well as the random effects pooled estimates for both ET and EPT. The pooled RRs of CRC were 0.79 (0.69-0.91) for ET ever use and 0.74 (0.68-0.81) for EPT ever use.…”
Section: Resultsmentioning
confidence: 99%
“…1). 4,5,13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Figure 2 shows the RR estimates reported by individual studies as well as the random effects pooled estimates for both ET and EPT. The pooled RRs of CRC were 0.79 (0.69-0.91) for ET ever use and 0.74 (0.68-0.81) for EPT ever use.…”
Section: Resultsmentioning
confidence: 99%
“…3,12,[19][20][21][22][23][24][25][26][27] In both a meta-analysis of eight such studies 27 and this meta-analysis incorporating 10 studies, a modest but statistically significant lower colorectal cancer incidence is associated with combined hormone therapy use. Such results agree with the current randomized clinical trial results regarding diagnosis rates but do not address the question of clinical relevance of the findings, since Abbreviation: SD, standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, female predominance and a diagnosis at old age have been observed in proximal colon cancer cases, while men have demonstrated a predominance of distal colon cancer. This evidence suggests that sex hormones may play a role in the pathogenic pathways of colorectal cancer and via subtypes, but whether this role is protective or not is controversial [3][4][5][6][7][8][9][10]. Interestingly, some studies have found positive associations between endogenous hormones and risk of colorectal adenocarcinoma [11,12].…”
Section: Introductionmentioning
confidence: 99%